Treating Clinically Node-Negative Insular Thyroid Carcinoma without Prophylactic Central Compartment Neck Dissection Is Associated with Decreased Survival Regardless of T Staging and Administration of Radioactive Iodine Therapy: The First Evidence. (16th October 2019) - Yu, Peng-Cheng; Shi, Xiao; Ma, Ben; Li, Cui-Wei; Tan, Li-Cheng; Hu, Wei-Ping; Wang, Yu; Wei, Wen-Jun; Wang, Yu-Long; Ji, Qing-Hai
Abstract : Forthe rare but aggressive insular thyroid carcinoma (ITC), there's no clear evidence to determine whether prophylactic central compartment neck dissection (CCND) is necessary for cN0 disease. This study provides the first evidence that treating cN0 ITC without prophylactic CCND is associated with decreased survival regardless of T staging and administration of RAI therapy. Background . Regarding the rare but aggressive insular thyroid carcinoma (ITC), the value of prophylactic central compartment neck dissection (CCND) for clinically node-negative (cN0) disease is unclear. We aimed to provide the first evidence. Methods . N0 and pN1a ITC patients were identified from the Surveillance, Epidemiology, and End Results database. These patients were divided into thyroid-surgery + CCND group (pN0/pN1a patients confirmed by CCND) and thyroid-surgery group (cN0 patients without CCND). Differences in overall survival (OS) and disease-specific survival (DSS) between the two groups were evaluated. Subgroup analyses were also conducted. Results . Of the overall 112 patients, 44 (39.3%) received CCND. On multivariate analyses, the lobectomy ± isthmusectomy / total-thyroidectomy (Lob/TT) group demonstrated poorer OS and DSS than the Lob/TT + CCND group (P < 0.05 ). When we separately analyzed patients treated by TT, multivariate analyses showed the TT group still revealed compromised OS and DSS than the TT + CCND group (P < 0.05 ). Furthermore, absence of CCND independently predicted decreased OS no matter whether radioactive iodine (RAI) was administered. Similar results were obtained for T3/T4 patients. Moreover, for T1/T2 patients receiving CCND, 0/12 died during the study period, while for T1/T2 patients without CCND, 8/23 (34.8%) died, 5/23 (21.7%) due to ITC. Conclusion . Regardless of T staging and RAI treatment, cN0-ITC patients without CCND had decreased survival compared with pN0/pN1a patients receiving CCND. Therefore, if a cN0 patient is diagnosed with ITC, prophylactic CCND may be considered as a secondary procedure (postoperatively diagnosed) or a primary procedure (preoperatively/intraoperatively diagnosed). Prospective studies are expected to validate the conclusion.